Review of Disruptive Digital Solutions in the Function of Maritime Transport and Safety Matters - Paladin, Zdravko; Šorović, Mira; Kapidani, Nexhat; Lukšić, Žarko; Mujalović, Rasim (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
The development and improvement of a vast range of disruptive information technologies (IT), including revolutionary Artificial Intelligence (AI) applications, requires the continuous collection of data from ship navigation and transport, transforming it into meaningful information for end-users. Contemporary AI-driven applications in the maritime industry are significantly advanced for processing data directly at the source, ensuring resilience, minimizing latency and errors, and reducing overall costs. This paper aims to present and investigate the features of the latest disruptive IT and AI use case technologies with their real impact on maritime trade, transport, surveillance, and safety based on data sharing and exchange platforms. The innovative solutions review wrapped most recent AI tools and features, concluding with the analysis of the practical improvements in the maritime industry and operating systems. By embracing AI, the maritime industry makes remarkable success with regards to competitive edge, better user and customers’ experiences, with an aim to achieve a higher operational efficiency.